2002
DOI: 10.1128/aem.68.02.928-932.2002
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Phosphatase Reporter Transposon for Identification of Genes Encoding Secreted Proteins in Gram-Positive Microorganisms

Abstract: We describe the construction of TnFuZ, a genetic tool for the discovery and mutagenesis of proteins exported from gram-positive bacteria. This tool combines a transposable element (Tn4001) of broad host range in gram-positive bacteria and an alkaline phosphatase gene (phoZ) derived from a gram-positive bacterium that has been modified by removal of the region encoding its export signal. Mutagenesis of Streptococcus pyogenes with TnFuZ ("FuZ" stands for fusions to phoZ) identified genes encoding secreted protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 40 publications
0
27
0
1
Order By: Relevance
“…Statistical significance was determined using a two-tailed paired t test with the StatView statistical analysis software (SAS Institute Inc., Cary, NC). (38), as well as previous reports of Tn4001 in HSC5 (15,38), demonstrated that transposition with Tn4001 results in single random integration of the transposon into the chromosome.…”
Section: Vol 77 2009 Stm In S Pyogenes 1855mentioning
confidence: 93%
See 1 more Smart Citation
“…Statistical significance was determined using a two-tailed paired t test with the StatView statistical analysis software (SAS Institute Inc., Cary, NC). (38), as well as previous reports of Tn4001 in HSC5 (15,38), demonstrated that transposition with Tn4001 results in single random integration of the transposon into the chromosome.…”
Section: Vol 77 2009 Stm In S Pyogenes 1855mentioning
confidence: 93%
“…Direct chromosomal sequencing of the transposon insertion, as opposed to subcloning and sequencing, allowed confirmation of single transposon insertions, whereas if multiple insertions had occurred in the chromosome, getting a single pure sequence off of the transposon would not have been possible. Previous reports have demonstrated the ability of a single copy of the Tn4001 transposon to insert into the HSC5 S. pyogenes genome (15,38). Each sequence was subsequently analyzed by comparison to known sequences in the databases of the National Center for Biotechnology Information.…”
Section: Methodsmentioning
confidence: 99%
“…The alkaline phosphatase reporter transposon (TnFuZ) developed by Gibson and Caparon allowed the study of proteins exported from Gram-positive bacteria; in S. pyogenes, two exported proteins without signal peptide have been described. In addition, it is known that some well-characterized proteins of S. pyogenes (a-enolase, glyceraldehyde-3-phosphate dehydrogenase) which are surface-exposed lack a defined export signal (Gibson & Caparon, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This sequence has been shown to contain a functional signal sequence directing either protein export or cell surface localization (Gibson & Caparon, 2002). The deposited Spy2033 sequence has an abnormally long 64 aa signal sequence.…”
Section: Summary Featuresmentioning
confidence: 99%